Moderating Role of Financial Policies on the Relationship between Tax Aggressiveness and Cash Holding - Setu Setyawan; Dhaniel Syam; Ahmad Juanda (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine and analyze the effect of tax aggressiveness on cash holding, and financial policies (leverage, capital intensity, inventory intensity) can moderate tax aggressiveness on cash holding.Design/Methodology/Approach: The population in this study was manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2017 period. The sample selected in this study was 106 companies that met the sample criteria. The research data were analyzed using simple regression analysis and multiple regression analysis.Research findings: The results of this study indicated that tax aggressiveness had a negative effect on cash holding, leverage had a significant negative effect in moderating the effect of tax aggressiveness on cash holding, the capital intensity had a significant positive effect in moderating the effect of tax aggressiveness on cash holding and inventory intensity had a positive significant effect in moderating the effect of tax aggressiveness on cash holding.Theoretical contribution/Originality: The inconsistency of previous studies regarding tax aggressiveness towards cash holding. This inconsistency is an important matter for further investigation, one of which is through the use of moderating variables that aim to measure strength. Therefore, this study correlates financial policies, which are the policy of leverage, capital intensity, and inventory intensity in companies conducting tax aggressiveness which determines the level of cash holding as a source of the company’s fund. There is hardly any research that used leverage, capital intensity, and inventory intensity as moderating variables, particularly capital intensity and inventory intensity.Practitioner/Policy implication: This research is potentially relevant to academics, researchers, and management. By examining the factors that affect the level of cash holding given the role of financial policy, this study reveals the way for further investigation of this topic with a set of micro and macro variables. This study provides insight into the principles of financial policy in moderating corporate tax aggressiveness to influence cash holding decisions.